A focus on adolescent peer violence and bullying in Europe, central Asia and Canada - Cosma, Alina; Molcho, Michal; Pickett, William (World Health Organization, 2024)
The Health Behaviour in School-aged Children (HBSC) study is a large school-based survey carried out every four years in collaboration with the WHO Regional Office for Europe. HBSC data are used at national/regional and international levels to gain new insights into adolescent health and well-being, understand the social determinants of health and inform policy and practice to improve young people’s lives. The 2021/2022 HBSC survey data are accompanied by a series of volumes that summarize the key findings around specific health topics. This report, Volume 2 in the series, focuses on adolescent peer violence and bullying, using the unique HBSC evidence on adolescents aged 11, 13 and 15 years across 44 countries and regions in Europe, central Asia and Canada. It describes the status of adolescent peer violence (bullying, cyberbullying and fighting), the role of gender, age and social inequality, and how adolescent bullying and fighting behaviour has changed over time. Findings from the 2021/2022 HBSC survey provide an important evidence benchmark for current research, intervention and policy-planning.
Keywords: HEALTH STATUS DISPARITIES; SOCIOECONOMIC FACTORS; GENDER EQUITY; ADOLESCENT HEALTH; BULLYING; CYBERBULLYING; VIOLENCE; Ageing; Genes & Society; Inclusive Society; Adolescent Psychology; Adolescents; CHILD DEVELOPMENT; Child and Adolescent Mental Health; Children/Youth; Developmental Psychology; Educational Psychology; Emotional/Mental Health; Global Health; PSYCHOLOGY; Mental Health/Psychosocial disability; Children; Development; Education; Gender; Health; Poverty; Youth